Complementary Chinese Herbal Medicine Therapy Improves Survival in Patients With Pemphigus: A Retrospective Study From a Taiwan-Based Registry - Wu, Po-Yuan; Li, Te-Mao; Chen, Shu-I.; Chen, Chao-Jung; Chiou, Jian-Shiun; Lin, Ming-Kuem; Tsai, Fuu-Jen; Wu, Yang-Chang; Lin, Ting-Hsu; Liao, Chiu-Chu; Huang, Shao-Mei; Lin, Yu-Ning; et al. (Frontiers in Pharmacology, 2020)
Pemphigus is a life-threatening and skin-specific inflammatory autoimmune disease, characterized by intraepidermal blistering between the mucous membranes and skin. Chinese herbal medicine (CHM) has been used as an adjunct therapy for treating many diseases, including pemphigus. However, there are still limited studies in effects of CHM treatment in pemphigus, especially in Taiwan. To more comprehensively explore the effect of long-term CHM treatment on the overall mortality of pemphigus patients, we performed a retrospective analysis of 1,037 pemphigus patients identified from the Registry for Catastrophic Illness Patients database in Taiwan. Among them, 229 and 177 patients were defined as CHM users and non-users, respectively. CHM users were young, predominantly female, and had a lesser Charlson comorbidity index (CCI) than non-CHM users. After adjusting for age, sex, prednisolone use, and CCI, CHM users had a lower overall mortality risk than non-CHM users (multivariate model: hazard ratio (HR): 0.422, 95% confidence interval (CI): 0.242-0.735, p = 0.0023). The cumulative incidence of overall survival was significantly higher in CHM users than in non-users (p = 0.0025, log rank test). Association rule mining and network analysis showed that there was one main CHM cluster with Qi-Ju-Di-Huang-Wan (QJDHW), Dan-Shen (DanS; Radix Salviae miltiorrhizae ; Salvia miltiorrhiza Bunge), Jia-Wei-Xiao-Yao-San (JWXYS), Huang-Lian (HL; Rhizoma coptidis; Coptis chinensis Franch.), and Di-Gu-Pi (DGP; Cortex lycii; Lycium barbarum L.), while the second CHM cluster included Jin-Yin-Hua (JYH; Flos lonicerae; Lonicera hypoglauca Miq.) and Lian-Qiao (LQ; Fructus forsythiae; Forsythia suspensa (Thunb.) Vahl). In Taiwan, CHMs used as an adjunctive therapy reduced the overall mortality to approximately 20% among pemphigus patients after a follow-up of more than 6 years. A comprehensive CHM list may be useful in future clinical trials and further scientific investigations to improve the overall survival in these patients.